The relevance of the number of categories in the hedonic scale to the Ghanaian consumer in acceptance testing - Addo-Preko, Emmanuel; Amissah, Joris Gerald Niilante; Adjei, Maame Yaakwaah Blay (Frontiers in Food Science and Technology, 2023)
The 9-point hedonic scale is the most widely used scale for consumer acceptance testing globally. The scale has nine categories with verbal anchors which are converted to a numerical scale with numbers assigned at equal intervals so that the psychological distance between successive scale points is equal. The verbal cues and number of categories assigned to them may not be relevant for Ghanaian consumers based on cultural differences. Using bread as an example, we used a 3 × 4 factorial design for bread types and scaling categories, to determine the number of categories in a hedonic scale that would be appropriate for Ghanaian consumers to use in a consumer acceptance test. Three commonly consumed breads in Ghana, tea bread, butter bread, and sugar bread were used. The number of categories in the scales we tested were the traditional 9-point, and three truncations of it; 7-point, 5-point, and 3- point scales. Each scale had verbal cues and numbers based on the traditional 9-point scale. Assessors rated their degree of overall liking followed by the degree of liking for appearance, flavor and texture of each bread sample. They further ranked the breads for preference. Simple t-tests, Analysis of variance and ranked order analyses were used to determine differences in liking scores for the breads across the different scales used. Regardless of the number of categories in the scales used, the order for product liking and preference rank order were the same; sugar bread > butter bread > tea bread. Attentiveness to the task of scoring the degree of liking was an important factor that impacted how the different scale lengths were used. When assessors are attentive to changes in scale length, they adjust their scores to fit the scale length and thus the number of categories in the scale length does not affect the acceptance score. The choice of scale length to use should be considered carefully in a consumer acceptance test.